Islamic Religious Education Teachers' Strategies in Integrating Islamic Character Values into the Learning Process - Mariyatul Kiftiyah; Roni Susanto; Imam Wahyudi (JISEI: Journal of Islamic Studies and Educational Innovation, 2025)
Islamic Religious Education (IRE) plays a strategic role in shaping students’ moral and spiritual character in formal education. However, the integration of Islamic character values into daily learning practices often faces various pedagogical and contextual challenges. This study aims to analyze the strategies employed by Islamic Religious Education teachers in integrating Islamic character values into the learning process. Using a qualitative descriptive approach, data were collected through classroom observations, in-depth interviews with IRE teachers, and documentation analysis. The findings reveal that teachers apply several key strategies, including the integration of character values into lesson planning, the use of exemplary behavior (uswah hasanah), habituation through religious routines, contextual learning methods, and reflective evaluation of students’ attitudes and behaviors. These strategies are supported by interactive learning models and a positive school culture that reinforces Islamic values both inside and outside the classroom. The study also identifies inhibiting factors, such as limited instructional time and diverse student backgrounds, as well as supporting factors, including teacher commitment and institutional support. Overall, the integration of Islamic character values through systematic and contextual strategies contributes significantly to the development of students’ religious attitudes and moral behavior. This study is expected to provide practical insights for educators in strengthening character-based Islamic education.